Balloon Pulmonary Angioplasty: A Treatment Option for Inoperable Patients with Chronic Thromboembolic Pulmonary Hypertension - Ogawa, Aiko; Matsubara, Hiromi (Frontiers in Cardiovascular Medicine, 2015)
In chronic thromboembolic pulmonary hypertension, stenoses or obstructions of the pulmonary arteries due to organized thrombi can cause an elevation in pulmonary artery resistance, which in turn can result in pulmonary hypertension. Chronic thromboembolic pulmonary hypertension can be cured surgically by pulmonary endarterectomy; however, patients deemed unsuitable for pulmonary endarterectomy due to lesion, advanced age, or comorbidities have a poor prognosis and limited treatment options. Recently, advances have been made in balloon pulmonary angioplasty for these patients, and this review highlights this recent progress.